Resource requirements for reintroducing elective surgery during the COVID-19 pandemic: modelling study. Issue 1 (21st December 2020) - Fowler, A J; Dobbs, T D; Wan, Y I; Laloo, R; Hui, S; Nepogodiev, D; Bhangu, A; Whitaker, I S; Pearse, R M; Abbott, T E F
Abstract: Background: The COVID-19 response required the cancellation of all but the most urgent surgical procedures. The number of cancelled surgical procedures owing to Covid-19, and the reintroduction of surgical acivirt, was modelled. Methods: This was a modelling study using Hospital Episode Statistics data (2014–2019). Surgical procedures were grouped into four urgency classes. Expected numbers of surgical procedures performed between 1 March 2020 and 28 February 2021 were modelled. Procedure deficit was estimated using conservative assumptions and the gradual reintroduction of elective surgery from the 1 June 2020. Costs were calculated using NHS reference costs and are reported as millions or billions of euros. Estimates are reported with 95 per cent confidence intervals. Results: A total of 4 547 534 (95 per cent c.i. 3 318 195 to 6 250 771) patients with a pooled mean age of 53.5 years were expected to undergo surgery between 1 March 2020 and 28 February 2021. By 31 May 2020, 749 247 (513 564 to 1 077 448) surgical procedures had been cancelled. Assuming that elective surgery is reintroduced gradually, 2 328 193 (1 483 834 – 3 450 043) patients will be awaiting surgery by 28 February 2021. The cost of delayed procedures is €5.3 (3.1 to 8.0) billion. Safe delivery of surgery during the pandemic will require substantial extra resources costing €526.8 (449.3 to 633.9) million. Conclusion: As a consequence of the Covid-19 pandemic, provision of elective surgery will be delayed and associated with increased healthcare costs. Abstract : The response to COVID-19 has required cancellation of all but the most urgent surgical procedures. This study modelled the cancellation and reintroduction of surgical care during the pandemic, and showed that more than 2 million procedures will be cancelled by March 2021. The costs of providing surgical care with heightened infection control procedures will be increased substantially.The response to COVID-19 has required cancellation of all but the most urgent surgical procedures. This study modelled the cancellation and reintroduction of surgical care during the pandemic, and showed that more than 2 million procedures will be cancelled by March 2021. The costs of providing surgical care with heightened infection control procedures will be increased substantially.The response to COVID-19 has required cancellation of all but the most urgent surgical procedures. This study modelled the cancellation and reintroduction of surgical care during the pandemic, and showed that more than 2 million procedures will be cancelled by March 2021. The costs of providing surgical care with heightened infection control procedures will be increased substantially. Much to do